Comparative efficacy on dogs of a single topical treatment with fipronil/(S)-methoprene or weekly physiological hygiene shampoos against Ctenocephalides felis in a simulated flea-infested environment - Beugnet, F. (EDP Sciences, 2012)
Flea infestations of pets continue to persist due to the lack of knowledge of flea biology and ecology. It is not unusual that pet owners believe regular hygiene, such as shampooing their dogs can replace regular insecticidal treatment. The objective of this study was to compare in a flea simulated environment, modelling exposure similar to that found in a home, that the use of regular physiological shampoo does not control fleas adequately when compared to a long acting topical formulation. Three groups of six dogs were formed: one untreated control group, one group treated monthly with the topical formulation of fipronil/(S)-methoprene, and a third group treated weekly with a hygiene shampoo. All dogs were infested with adult unfed Ctenocephalides felis fleas (200 ± 5) on Days -28 and -21. Each animal’s sleeping box was fitted with a plastic cup mounted to the inside roof of the box. The sleeping bench of each animal was covered with a carpet to accommodate flea development. The dogs were maintained in their kennels throughout the study. In order to maintain the environmental flea challenge, C. felis pupae (100 ± 5) were placed in the plastic cup in each animal’s sleeping box on Days -14, -7, 0, 7, 14, 21, 28, 35 and 42. The dogs were combed and fleas counted weekly on Days -1, 3, 10, 17, 24, 31, 38, 45, and 51. The fleas were placed immediately back on the dogs. On Day 60, fleas were counted and removed. Flea infestations in the untreated control group at each count averaged between 46.2 and 74.2 fleas throughout the study. The average number of fleas infesting dogs was significantly different (p < 0.05) between the untreated and the two treatment groups and between the two treatment groups at all counts throughout the two months study (Days 3, 10, 17, 24, 31, 38, 45, 51 and 60). The efficacy was never below 99.1% in the fipronil/(S)-methoprene group, and efficacy in the shampoo group was never above 79.2%. Weekly shampooing in treatment group 3 was intentionally delayed after Day 42, to evaluate wether missing a weekly bath would affect the flea population. The Day 48 data indicate that forgetting or delaying a single weekly shampooing resulted in a clear increase in flea numbers and a significant decrease in efficacy from 68.2% to 34.8%. The fipronil(S)/methoprene treatment allowed a continuous control as demonstrated by the high efficacy against fleas, and also the number of flea-free dogs on seven of the nine weekly assessments, in spite of what was essentially a continuous flea challenge model.